Porphyromonas gingivalis Gingipains Selectively Reduce CD14 Expression, Leading to Macrophage Hyporesponsiveness to Bacterial Infection - Wilensky, Asaf (J Innate Immun, 2015)
Cysteine proteases (gingipains) from Porphyromonas gingivalis are key virulence factors in chronic periodontitis. Innate immune receptors CD14, Toll-like receptor (TLR) 2 and TLR4 are important in P. gingivalis recognition. We examined the ability of gingipains to cleave CD14, TLR2 and TLR4, and the consequences for the cellular response to bacterial challenge. Macrophages were exposed to Arg (RgpA and RgpB)- and Lys (Kgp)-gingipains, and residual expression of TLR2, TLR4 and CD14 was determined by flow cytometry. The cellular response to live bacteria following exposure to purified gingipains was evaluated by TNFα production and bacterial phagocytosis. RgpA and Kgp decreased CD14 detection in a concentration (p = 0.0000002)- and time (p = 0.03)-dependent manner, whereas RgpB had no significant effect. TLR2 and TLR4 expression were unaffected. Reduction in CD14 expression was more efficient with Lys-gingipain than with Arg-gingipain. A reduced CD14 surface level correlated with decreased TNFα secretion and bacterial phagocytosis following challenge with live P. gingivalis, but the response to heat-killed bacteria was unaffected. Therefore, gingipains reduce CD14 expression without affecting expression of the bacterial-sensing TLRs. Reduced CD14 expression depends on the gingipain hemagglutinin/adhesion site and results in macrophage hyporesponsiveness to bacterial challenge. Further studies are needed to determine if reduced CD14 expression is linked to periodontitis induced by P. gingivalis.